Investigation of transverse motion of concealed scatterer using correlation of speckled speckles from static surface layer - Vinu R.V.; Nair G.G.; Naik D.N.; Jakobsen M.L.; Hanson S.G.; Singh R.K. (My University, 2025)
Speckle-based techniques have noteworthy applications in the field of material science, surface characterization, determining mechanical displacements, biological activity in diffuse layer, imaging through turbid layer etc. The passage of coherent light through a diffuse layer generates a random speckle pattern, which have the inherent feature of carrying information associated with the diffuse layer. Dynamic laser speckle associated with the displacements of scattering surface has prominent impacts in the study of biological activity inside the diffuse layer. Investigations are progressing in the direction of exploring the dynamical properties associated with speckled speckles and its applications in imaging and characterization scenarios. In this work, we theoretically and experimentally study the dynamical properties of speckles through a static scattering layer using intensity correlation. The displacement (transverse or angular) produced in the concealed scatterer generates the dynamic speckle pattern which is observed through a second static diffuser. We expect to find applications of this investigation into the tracking objects hidden in the diffuse layer, measuring biological activity in diffuse layer, displacement measurements, etc. © 2018 SPIE.